A phytotherapeutic approach to hinder the resistance against clindamycin by MRSA: in vitro and in silico studies - Amal Mayyas; Ali Al-Samydai; Nehaya Al-Karablieh; Waleed A Zalloum; Deniz Al-Tawalbeh; Farah Al-Mamoori; Rula A. Amr; Hamdi Al Nsairat; Simone Carradori; Lidia Kamal Al-Halaseh; Talal Aburjai (Future Science OA)
Aims This study investigates the potential effects of essential oils (EOs) in enhancing the efficacy of clindamycin against Methicillin-resistant Staphylococcus aureus (MRSA) using in vitro and computer simulations. The research seeks to identify essential oils that exhibit synergistic activity with clindamycin and determine their potential key active components.Materials and Methods Essential oils commonly used in traditional medicine were tested for their antimicrobial activity against MRSA. The minimum inhibitory concentration (MIC) was determined using in vitro microdilution assays. A synergistic test with clindamycin was performed, and molecular docking studies evaluated the interaction between a key compound (trans-cinnamaldehyde) and MRSA protein.Results EOs from Cinnamomum verum, Rosmarinus officinalis, Salvia officinalis, and Thymus vulgaris demonstrated significant inhibitory and synergistic activities against MRSA, standard strain, and human clinical isolates. Gas Chromatography/Mass Spectroscopy identified trans-cinnamaldehyde, eucalyptol, and thymol as prominent antibacterial compounds. Molecular docking studies confirmed trans-cinnamaldehyde’s strong binding to MRSA’s AgrA protein, elucidating its enhanced efficacy.Conclusion The study underscores the potential of plant-based therapies to augment the effectiveness of conventional antibiotics like clindamycin in combating MRSA and addressing antibiotic resistance by integrating traditional plant remedies with modern medical approaches.